Ethnomathematics: Exploring Traditional Games in Mathematics Learning - Lois Oinike Tambunan; Izwita Dewi; Lasker Pangarapan Sinaga (Universitas Teknokrat Indonesia, 2025)
This study aims to examine ethnomathematics in traditional games, particularly among the Batak Toba ethnic group, where mathematical concepts such as geometry, number operations, relationships between lines, the concept of congruence, probability, number patterns, and speed are present. The traditional games analyzed in this study include Marsitekka, Margala, and Pocca Piring. This research employs qualitative descriptive approach,where the subjects of this research are the three types of traditional games mentioned earlier. The data collection techniques used in this study include observation, field notes, and documentation. Integrating traditional games into mathematics learning provides benefits by visualizing mathematical concepts in a tangible form, making it easier for students to understand mathematical learning.